Karakterisasi dalam Simbolisasi Hewan pada Peribahasa Madura - Muhri (Tadris Bahasa Indonesia, Fakultas Tarbiyah, Institut Agama Islam Negeri Madura, 2024)
This study is based on the assumption that symbols in society represent the way of thinking of the society. With this background, the purpose of this study is to describe the use of animal symbols and animal characterization in Madurese proverbs. With the basic theory of semiotics, this study is a descriptive-qualitative study. Data collection was carried out by document study. Data analysis used content analysis methods/techniques. Based on the results of the study, it was concluded that the animal symbols in Madurese proverbs include domestic animals, both livestock, pets and non-pets and wild animals. Animals that consistently symbolize positive and negative character values ​​and tend to continue to show that these characters are manifestations of the subconscious of the Madurese people in viewing animal symbols in culture. Animals that have negative character values ​​are in line with expressions such as curses, praise, etc. that use animal symbols.